Epigenetics disruptions enabled by porphyrin-derived metal-organic frameworks disarm resistances to sonocatalytic ROS anti-tumor actions - Yan Zhang; Dou Du; Chao Fang; Xin Yu; Yujia Fang; Xinyu Liu; Di Ou; Haohao Yin; Hui Liu; Taixia Wang; Lu Lu; Xiaolong Li; et al. (Fundamental Research)
Post-transcriptional epigenetic modifications provide numerous implications for tumor progression, metastasis and recurrence, which also pose resistances to reactive oxygen species (ROS)-based anti-tumor. Herein, we proposed an epigenetic deubiquitination disruption strategy to disarm the ubiquitination-deubiquitination balance-induced resistances to ROS production and ROS-based anti-tumor action for potentiating sonodynamic treatment (SDT) efficiency. To end it, porphyrin-derived metal-organic framework (MOF) sonocatalytic nanoplatforms were developed to load deubiquitination inhibitors (i.e., Auranofin). Ultrasound-triggered Auranofin release from PCN224@Au has been validated to blockade the deubiquitinating process and drive proteasome-mediated target protein degradation. The epigenetic deubiquitination disruption not only synergized with MOF-mediated sonocatalytic ROS production, but also inactivate deubiquitinating enzymes, blockade the deubiquitination process and further remove these resistances, both of which mutually behaved as reciprocal impetuses to significantly magnify SDT outcomes against liver cancers. Such a deubiquitination-engineered disruption approach finds an unprecedented pathway to disarm deubiquitination-induced resistances to SDT and other ROS-based anti-tumor means, which also enlightens us to establish other post-transcriptional epigenetic modification disruption strategies to re-program the tumor microenvironment and elevate the anti-tumor efficiency of various treatment methods (e.g., immunotherapy).